ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENJUALAN DI INDRAKO SWALAYAN TELUK KUANTAN - Rogi Gusrizaldi; Eka Komalasari (UIR Press, 2016)
Sales is an absolute requirement continuity of a business, because it will get the sales profits. The higherthe sales, the profit didapatpun will be maximized. To achieve this goal it is very necessary efforts so thatconsumers have the appeal and loyal nature of shopping in the business unit. A company will not developif unable to sell the products produced, instead, a company is able to exist in the competition. Accordingto Basu Swastha (2001:8) sales is the science and art of personal influence made by the seller to inviteother people to be willing to buy goods offered. The factors that affect penjulalan is the condition andability of sellers, market conditions, capital and organizational conditions of the company. This studyaims to determine the factors that influence the level of sales in Supermarkets Indrako Teluk Kuantan.This type of research is the type of quantitative research, the research emphasizes on the analysis ofnumerical data (numbers) are processed by the method statiska, so as to obtain an assessment of eachvariable. Methods of data collection was done by a list of questions (questionnaire), interviews,observation, documentation. And using a sampling technique that uses accidental sampling technique forsampling in 40 consumers. The results of the four indicators are quite good. Suggestions writer is toreorganize and improve again the factors that affect the level of sales by fixing four independentvariables are perceived masi less than the maximum.